Direct Sensing in Liquids Using Whispering‐Gallery‐Mode Droplet Resonators. Issue 12 (17th September 2014) - Avino, Saverio; Krause, Anika; Zullo, Rosa; Giorgini, Antonio; Malara, Pietro; De Natale, Paolo; Loock, Hans Peter; Gagliardi, Gianluca
<x xml:space="preserve">Abstract</x> Liquid droplets suspended by the tip of a thin wire, a glass capillary, or a needle form high‐Q optical resonators, thanks to surface tension. Under gravity equilibrium conditions, the maximum drop diameter is approximately 1.5 mm for paraffin oil (volume ∼ 0.5 μL) using, for instance, a silica fiber with 250 μm thickness. Whispering gallery modes are excited by a free‐space near‐infrared laser that is frequency locked to the cavity resonance. The droplet cavity serves as a miniature laboratory for sensing of chemical species and particles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>